Aquaporin activity of barley tonoplast intrinsic proteins is involved in the delay of the coalescence of protein storage vacuoles in aleurone cells - Lee, Sung-Eun (Journal of plant physiology, 2020)
Copyright © 2020 Elsevier GmbH. All rights reserved.